Comparative evaluation of different power management strategies of a stand-alone PV/Wind/PEMFC hybrid power system - DURSUN, ERKAN; KILIÇ, OSMAN (ELSEVIER SCI LTD, 2012)
This study presents different power management strategies of a stand-alone hybrid power system. The system consists of three power generation systems, photovoltaic (PV) panels, a wind turbine and a proton exchange membrane fuel cell (PEMFC). PV and wind turbine is the main supply for the system, and the fuel cell performs as a backup power source. Therefore, continuous energy supply needs energy storing devices. In this proposed hybrid system, gel batteries are used. The state of charge (SOC), charge-discharge currents are affecting the battery energy efficiency. In this study, the battery energy efficiency is evaluated with three different power management strategies. The control algorithm is using Matlab-Simulink (R). (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Stand-alone hybrid power system; Energy management; Battery energy efficiency; PERFORMANCE; TURBINE; STORAGE; STACK; MODEL